Isolating the speed factor is crucial in gait analysis for Parkinson’s disease - Patoz, Aurélien; Malatesta, Davide; Burtscher, Johannes (Frontiers in Neuroscience, 2023)
Parkinson's disease (PD) is characterized by an alteration of the walking gait, frequently including a slower self-selected walking speed (SSWS). Although the reduction of walking speed is inherent to people with PD, such speed reduction also represents a potential confounding factor that might partly explain the observed gait differences between PD and control participants. In this study, each participant walked along a 25m level corridor during which vertical ground reaction force signals were recorded using shoes equipped with eight pressure sensors. Vertical ground reaction force signals (using statistical parametric mapping) and temporal and kinetic variables as well as their related variability and asymmetry (using Student’s t-test) were compared between PD (n=54) and walking-speed-matched control subjects (n=39). Statistical parametric mapping did not yield significant differences between PD and control groups for the vertical ground reaction force signal along the walking stance phase. While single support, double support, and stance times were significantly more variable and asymmetric for PD than for the control group (P≤0.05), stride time was similar (P≥0.07). These results indicate that at matched SSWS, PD patients adopt a higher cadence than control participants. Moreover, the temporal subdivision of the walking gait of people with PD is similar to healthy individuals but the coordination during the double support phase is different. Hence, this study indicates that isolating the speed factor is crucial in gait analysis for PD.